European Society for Neurogastroenterology and Motility Consensus on Gastroparesis: What Issues Remain Unresolved? - A. A. Sheptulin; A. S. Trukhmanov; O. A. Storonova; D. E. Rumyantseva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2022)
Aim: to analyse the document of the European Society for Neurogastroenterology and Motility consensus on gastroparesis, held in 2020.Key findings. The evaluation of the voting results on the submitted statements of the consensus meeting shows that there is a high level of agreement among the experts regarding the definition of gastroparesis, the main diseases in which it occurs, and the existing diagnostic methods. At the same time, there is a divergence of views regarding the role of individual pathogenetic factors of gastroparesis and their relationship with clinical symptoms, as well as the effectiveness of drugs of various groups and other treatment methods.Conclusion. The pathophysiological mechanisms of gastroparesis and the effectiveness of various treatment methods need further research.